Self-Healing Nano-Concrete for Futuristic Infrastructures: A Review - Shaheen, N. (Springer Science and Business Media Deutschland GmbH, 2022)
Spontaneous self-healing is an imperative requisite for sustaining the structural life of cementitious composites substituting the fissures and pores by restricting the ingress of hazardous chemicals. The intrinsic self-healing ability of cementitious composites is inadequate that enforcing the submissions of extrinsic self-healing for imparting resilience, durability and survivability. Profoundly, robust extrinsic self-healing action can be accomplished by arresting the cracks at the nano-level via inhibiting their progression at micro- and macro-levels. The exceptional chemical and physical configuration of nanomaterials facilitates their potential application as self-healing agent for inducing inherent self-healing characteristics inside the cementitious composites at nano-level. These self-healing nano-modificient includes expansive agents, nano-polymers, secondary raw materials, nano-metallic and nano-chemical insertions. However, the applications of these nano-modificent agents are explored in the refining of structural, mechanical and electromechanical properties of concrete, extensively. Owing to development of biological self-healing concrete, a scientific shift has been observed in attaining self-healing at nano-level. In this review, the existing application of nano-modificent agents for imparting self-healing characteristics inside the cementitious systems is discussed in addition to future challenges and prospects. Â© 2022, King Fahd University of Petroleum & Minerals.